Teori och typologi: Om förhållandet mellan makrosociologi, institutionella sfärer och social handling (Sociologisk Forskning, 1994)
Theory and typology. Macrosociology, institutional spheres and social actionThe conceptual triad ’state-market-civil society’ is taken as point of departure for a discussion of the broader issue of the uses of typologies in sociology. It is argued that in order to avoid being subordinated to politically loaded notions pervading public discourse, a genuine sociological typology should meet two demands; its dimensions should be derived from a macro-sociological theory, and it should be underpinned by a micro-sociological theory of action. In this way, a typology will serve as a pipeline between micro and macro theories, and also as a checking point for estimating the coherence between these two levels of analysis. As an illustration, Mary Douglas’ grid-group model is introduced. This typology is derivable from Durkheim’s macro-sociology, but it has a weak microfoundation. Two theories of action are discussed and compared; the theory of rational choice and the theory of interaction rituals. After demonstrating that the theory of rational choice is incommensurable with the ”multi-rational” premises of the grid-group model, itis indicated that an elaboration of the Goffmanian theory of interaction rituals would constitute a viable micro-foundation for the grid-group model. Finally, it is concluded that from the point of view of grid-group, ’civil society’ is a highly ambiguous category that should be replaced by the categories of ’community’ and ’isolate’.